A bibliometric analysis of undergraduate theses from the School of Library and Information Studies from 2010-2014 an exploratory study - Balaquit, Jessica Patricia S.; Bugnosen, Marianne G. (School of Library and Information Studies, University of the Philippines, Diliman, 2015)
This study focused on the use of bibliometrics to perform qualitative research on the citations used in the undergraduate theses of UP SLIS from 2010-2014. The first step was to create a citation index that contains the article titles, authors, and journal titles used by the undergraduate students. Using existing tools such as BibExcel and VOSViewer, the researchers were able to convert the citation index from .xlsx file to .net file, producing bibliometric maps that reflect the relationships of the authors to each other and to the research tracks of UP SLIS.